Surgical Treatment for Chronic Pancreatitis: Past, Present, and Future - Stephanie Plagemann; Maria Welte; Jakob R. Izbicki; Kai Bachmann (Gastroenterology Research and Practice)
The pancreas was one of the last explored organs in the human body. The first surgical experiences were made before fully understanding the function of the gland. Surgical procedures remained less successful until the discovery of insulin, blood groups, and finally the possibility of blood donation. Throughout the centuries, the surgical approach went from radical resections to minimal resections or only drainage of the gland in comparison to an adequate resection combined with drainage procedures. Today, the well-known and standardized procedures are considered as safe due to the high experience of operating surgeons, the centering of pancreatic surgery in specialized centers, and optimized perioperative treatment. Although surgical procedures have become safer and more efficient than ever, the overall perioperative morbidity after pancreatic surgery remains high and management of postoperative complications stagnates. Current research focuses on the prevention of complications, optimizing the patient’s general condition preoperatively and finding the appropriate timing for surgical treatment.